Positive regulation of HIF-1A expression by EBV oncoprotein LMP1 in nasopharyngeal carcinoma cells. Issue 1 (1st November 2016) - Sung, Wei-Wen; Chu, Yi-Chih; Chen, Peir-Rong; Liao, Ming-Hui; Lee, Jeng-Woei
Highlights: LMP1 up-regulates HIF-1A transcription and post-transcription in NPC cells. Down-regulation of RNA-destabilizing proteins contributes to stabilize HIF-1α mRNA. LMP1 facilitates HIF-1A promoter activity and positive auto-regulation of HIF-1α. Abstract: Latent membrane protein 1 (LMP1) is a pivotal viral oncoprotein that contributes to the carcinogenesis of Epstein–Barr virus (EBV)-associated malignancies, including nasopharyngeal carcinoma (NPC). We investigated the regulation of hypoxia-inducible factor 1-α (HIF-1α) by LMP1. In NPC cells, we found that LMP1 significantly enhanced the HIF-1α mRNA level, and not only the protein amount as described previously. Mechanistically, the stability of the HIF-1α transcript was remarkably prolonged by LMP1 via reduced expressions of RNA-destabilizing proteins tristetraprolin (TTP) and pumilio RNA-binding family member 2 (PUM2) through C-terminal activation region 1 (CTAR1) and CTAR3 interaction with the ERK1/2 and STAT3 signaling pathways, respectively, in parallel with hindrance of PUM2 binding to the HIF-1α mRNA 3′-untranslated region (3′-UTR). On the other hand, HIF-1A promoter activity was also obviously facilitated by the LMP1 CTAR1-recruited ERK1/2/NF-κB pathway. Intriguingly, in this scenario, augmented HIF-1α further exhibited positive auto-regulation of its own gene transcription. Our results showed the first time that LMP1 directly up-regulates HIF-1A transcription and post-transcription in NPC cells, in addition to providing evidence of an increase in the HIF-1α mRNA level caused by a tumor-associated virus under normoxic conditions.